Development and Evaluation of a Biology Learning Module Integrating Microlearning Videos for Teaching the Human Immune System - Andi Tirta Angraeni; Ismail Ismail; Faisal Faisal; Firdaus Daud; Rachmawaty Rachmawaty (Sakura Digital Nusantara, 2026)
Purpose: This study was done to create and check a Biology learning module that uses videos to teach people about the human immune system. The goal was to see if this module is really good if it is useful and if it actually works. The study looked at the Biology learning module and the immune system to find this out. Methods: This study employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with Grade XI students at SMA Negeri 4 Bulukumba, Indonesia. The module was validated by two experts and evaluated for practicality through questionnaires completed by two biology teachers and 23 students. Its effectiveness was assessed with 41 students (23 in the experimental class and 18 in the control class). Data were analyzed using Gregory’s validity coefficient, descriptive percentage analysis, and normalized gain (N-gain). The ADDIE model provided a systematic framework for developing a valid, practical, and effective biology learning module integrated with microlearning videos. Findings : T he developed module achieved a Gregory validity coefficient of 1.00, indicating very high validity. Teacher and student practicality scores reached 91.88% and 80%, respectively, indicating that the module is practical for classroom use. Furthermore, the experimental class achieved a higher N-gain score (0.72, high) than the control class (0.49, moderate), demonstrating that integrating microlearning videos into the Biology module effectively improved students' learning outcomes on the human immune system. Research Implications: The findings suggest that the developed module can serve as an effective instructional resource for teaching abstract Biology concepts while supporting independent and technology-enhanced learning in senior high schools. Originality: Unlike previous studies that primarily examined microlearning videos as standalone instructional media, this study integrates microlearning videos into a systematically developed Biology learning module and comprehensively evaluates its validity, practicality, and effectiveness, thereby contributing to the development of innovative Biology teaching materials for senior high school education.